Unilateral Termination Of Employment (PHK) By PT. Pong Codan Indonesia (PCI) As Reviewed In The Connection With Government Regulation Number 35 Of 2021 Concerning Fixed-Term Employment Agreements, Outsourcing, Working Hours And Rest Hours, And Termination - Dicky Muhammad Gibran; Muhamad Abas; Yuniar Rahmatiar (Journal of Law, Politic and Humanities, 2026)
Unilateral termination of employment constitutes a fundamental issue in industrial relations, reflecting the imbalance of bargaining power between employers and workers. The state intervenes through labor regulations, particularly Law Number 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law Number 2 of 2022 on Job Creation as Law and Government Regulation Number 35 of 2021 concerning Fixed-Term Employment Agreements, Outsourcing, Working Time and Rest Time, and Termination of Employment, to ensure legal protection for workers. This study examines how termination of employment is regulated under Government Regulation Number 35 of 2021 and how the panel of judges considered unilateral termination cases in Decision Number 16/Pdt.Sus-PHI/2025/PN Bdg. The research employs a qualitative method with a normative legal approach through literature study of statutory regulations and court decisions. Government Regulation Number 35 of 2021 regulates termination of employment comprehensively as a last resort with strict procedures. In Decision Number 16/Pdt.Sus-PHI/2025/PN Bdg, the panel of judges declared that the fixed-term employment agreement had transformed into an indefinite-term employment agreement and that the termination was null and void. However, a contradiction arises as the employment relationship was ultimately terminated on grounds of efficiency solely based on Article 100 of Law Number 2 of 2004 without considering Constitutional Court Decision Number 19/PUU-IX/2011, whereas the efficiency provisions within that Constitutional Court Decision cannot justify the termination of employment of the Plaintiffs whose status had been established as indefinite-term, thus the legal basis employed was inaccurate and entirely without juridical foundation, ultimately failing to provide optimal legal protection for workers.